2015
DOI: 10.1111/ijd.12703
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of subclinical left ventricular dysfunction in patients with psoriasis by speckle tracking echocardiography: A Speckle Tracking Study

Abstract: Using 2-D strain imaging, we have demonstrated that patients with psoriasis have lower LV functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…Previous studies revealed the association between the duration of psoriasis or its severity, as assessed by the PASI score, and the degree of the left ventricular systolic impairment . The current investigation confirmed this relationship only with respect to the latter.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Previous studies revealed the association between the duration of psoriasis or its severity, as assessed by the PASI score, and the degree of the left ventricular systolic impairment . The current investigation confirmed this relationship only with respect to the latter.…”
Section: Discussionsupporting
confidence: 78%
“…Available data emerging from a few recent publications indicate that psoriatic patients are characterized by subclinical myocardial dysfunction as expressed by impaired left ventricular (LV) deformation (reflecting myocardial contractile properties) and diastolic indices, and abnormal left atrial mechanics. All these alterations occur independent of accompanying comorbidities, such as ischaemic heart disease, hypertension, diabetes mellitus, obesity or renal failure . Furthermore, the improvement in cardiac performance paralleling an amelioration in psoriasis severity achieved by biological therapy was demonstrated …”
Section: Introductionmentioning
confidence: 98%
“…In the present study, the E/E' ratio in the psoriatic patients was significantly higher than in controls. Similarly, Bülbül Sen et al [5] found a higher E/E' ratio in their psoriasis group. In addition, the present study found that serum chemerin levels correlated positively with the E/E' ratio and negatively with the E' and E'/A' ratios.…”
Section: Discussionmentioning
confidence: 72%
“…Psoriasis is a chronic inflammatory disease of the skin, affecting 2-3% of the world's population [4]. It is known that psoriasis is associated with earlier development of atherosclerosis and a higher prevalence of subclinical left ventricular (LV) dysfunction, even in those without traditional cardiovascular (CV) risk factors [5]. The main mechanism behind these conditions is the chronic inflammatory process of psoriasis [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…rheumatoid arthritis, psoriasis, Crohn's disease) can also cause an expansion and proinflammatory transformation of epicardial adipose tissue. Transmission of the inflammatory process to the underlying myocardium in these disorders leads to cardiac fibrosis and a destruction of microvascular structures, and thus, an impairment of ventricular distensibility and diastolic filling abnormalities …”
Section: Evolution Of Obesity‐related Heart Failure With Preserved Ejmentioning
confidence: 99%